Mechanochemistry: New Tools to Navigate the Uncharted Territory of “Impossible” Reactions - Cuccu, Federico; De Luca, Lidia; Delogu, Francesco; Colacino, Evelina; Solin, Niclas; Mocci, Rita; Porcheddu, Andrea (ChemSusChem, 2022)
Mechanochemical transformations have made chemists enter unknown territories, forcing a different chemistry perspective. While questioning or revisiting familiar concepts belonging to solution chemistry, mechanochemistry has broken new ground, especially in the panorama of organic synthesis. Not only does it foster new “thinking outside the box”, but it also has opened new reaction paths, allowing to overcome the weaknesses of traditional chemistry exactly where the use of well‐established solution‐based methodologies rules out progress. In this Review, the reader is introduced to an intriguing research subject not yet fully explored and waiting for improved understanding. Indeed, the study is mainly focused on organic transformations that, although impossible in solution, become possible under mechanochemical processing conditions, simultaneously entailing innovation and expanding the chemical space. Mission impossible: Mechanosynthesis is erroneously perceived as an enabling tool for only making greener well‐known solution‐based processes. Modern mechanochemistry is, above all, an effective tool to open synthetic paths not accessible by following conventional and well‐known pathways already reported in the literature for the classical chemistry in solution. Mechanical stimuli promote uncharted reaction pathways, making it possible to design and develop effective, successful synthetic protocols previously classified as “impossible reactions”.